A high-precision positioning method for deep-towed multichannel seismic arrays - Wei, Zhengrong; Pei, Yanliang; Zhu, Xiangqian; Liu, Kai; Zhang, Xiaobo; Zong, Le; Li, Xinyu (Frontiers in Marine Science, 2024)
Kuiyang-ST2000 is a deep-towed multichannel seismic system that provides high-resolution exploration of sub-seabed geological formations. Due to the uncertainty of the sound speed at full ocean depth, the travel-time positioning of sea surface reflected waves still has flaws in positioning arrays. This research reveals that the average sound speed of seawater selected for computing the array position only affects the vertical displacement of the arrays. thus, a polynomial fitting method is proposed to position the arrays. Because the nonuniform mass distribution complicates the array shape, first, the weight of the digital transmission unit is balanced by one designed floater so that the array shape becomes a simple convex curve during towing conditions. Afterward, one general sound speed is used to calculate the initial array position; then, the polynomial fitting method is used to tune the sound speed so that the seismic source and hydrophones are on the same convex curve. Finally, an accurate array position is calculated by the proposed positioning method, and the submarine shallow strata are imaged at a high resolution.